Cross-Layer Performance Analysis of Post-Quantum Digital Signatures in Urban 5G-V2X Communications - Teixeira, Caio; Henriques, Marco Amaral (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
As quantum computing threatens existing public key algorithms within the next decade, transitioning to post-quantum cryptography (PQC) is imperative. This paper evaluates the physical and MAC layer impacts of adopting PQC in 5G-V2X networks. Using the WiLabV2Xsim simulator in a 3GPP-compliant urban scenario, we assess network degradation across different post-quantum signature algorithms, and provide evidence that algorithms with large signatures cause severe radio channel saturation and latency, while compact alternatives introduce heavy computational bottlenecks. We conclude that direct ECDSA replacement is unfeasible, and that securing future V2X systems requires fundamental changes on the current PKI paradigm.